Analyzing The Changing Role Of Educators Under Nep 2020 Implications For Pedagogical Innovation And Continuous Professional Learning - Arun B Prasad (Journal of Informatics Education and Research, 2025)
The NEP 2020 redefines the roles of teachers in India by prioritizing "competency-based curricula, inclusive pedagogy, and systematic continuous professional development (CPD)". The NEP 2020 establishes new national standards for teachers & highlights the importance of ongoing professional development, advocating for systematic CPD programs and institutional support mechanisms like DIKSHA and NISHTHA. Numerous recent studies highlight the shift from input-centric to outcome-oriented teacher education and the necessity for competency-based, practice-oriented training. Research indicates that although the policy establishes frameworks for Continuous Professional Development (CPD) and pedagogical innovation, its implementation differs among states and institutions, encountering limitations in capacity, resources, and infrastructure. Numerous empirical studies indicate that continuous professional development (CPD) enhances teacher confidence and the implementation of active, student-centered pedagogies; yet, enduring influence necessitates mentorship, communities of practice, and ongoing support. Recent examples of implementing NEP objectives include policy-aligned programs from CBSE and state agencies focused on teacher capacity building and domain-specific continuing professional development (CPD). This paper analyzes the impact of NEP 2020 on educators' obligations, investigates pedagogical innovation and continuous professional development (CPD) processes, and offers an empirical study comparing primary and secondary teachers regarding CPD engagement and the implementation of pedagogical innovations. The research employs a sample of 120 educators (60 from primary and 60 from secondary schools), utilizing descriptive statistics, an independent-samples t-test for continuing professional development hours, and a chi-square test for the adoption of innovations. The study concludes with recommendations for policy and practice to implement the teacher-related elements of the NEP.